Restoring the Asian Silk Route: Toward an integrated Asia - Biswa N. Bhattacharyay; Prabir De (Asian Development Bank Institute (ADBI), 2009)
Until the 13th century, the ancient Silk Route of Asia was the world's most important cross-border artery, at a time when Asia was a major trade and economic center of the world. The Silk Road refers to an extensive pan-Asia interconnected network of trade routes across the Asian continent connecting Eastern, Southern, Central, and Western Asia with the Mediterranean, including North Africa and Europe. Over the past decades of globalization, Asia has re-emerged as one of the major economic power of the world. Many Asian economies have become an integral part of international production networks and have benefited from increased growth, trade, and investment. However, Asia's huge economic potential remains largely untapped due to lack of region-wide connectivity. This paper argues that lack of full regional connectivity is one of the major constraints hindering regional growth and integration in Asia, as well as with the rest of the world. One of the conclusions of this paper is that Asia must strengthen its physical connectivity to make it a conduit for international trade though restoring Asian Silk Route. This paper deals with current trade and transport integration issues among the countries in Asia as well as challenges that need to be addressed in order to achieve regional connectivity through an Asia-wide transport infrastructure.
Keywords: F1; F5; R1; R4; 330